Pendampingan Pengaturan Menu Sehat Seimbang Pra Pertandingan di Sahabat Basketball Club - Yade K. Yasin; Nurul Ichsania; Sugirah Nour Rachman; Sanrebayu Sanrebayu; Hadijah Alimuddin (Abdimas Toddopuli: Jurnal Pengabdian Pada Masyarakat, 2025)
The assistance program on balanced pre-competition meal planning for athletes of Sahabat Basketball Club was conducted to improve their understanding and skills in preparing nutritional intake suitable for physical demands prior to competition. The program involved 25 adolescent basketball athletes and was implemented through three core approaches: education, mentoring, and socialization. Evaluation was carried out using pre- and post-test assessments to measure changes in knowledge and practical skills related to food selection, nutrient composition, and pre-match meal timing strategies. Results showed a significant improvement in post-test scores compared to pre-test results, with an average increase of approximately 30 points, indicating enhanced understanding and behavioral changes toward more structured nutritional practices. This program demonstrates that educational interventions combined with direct mentoring can provide positive and sustainable impacts on athletes’ readiness for competition. Therefore, similar initiatives are recommended to be continued as an integral part of athlete development programs.